Assessment of Tourism in Hungary Between 2004-2022 in the Light of Regional Differences - Gyurkó, Ádám; Zoltán, Bujdosó; Csaba, Hamza (Acta Carolus Robertus, 2023)
The objective of the study is to present the tourism performance of Hungary within the European Union between 2004 and 2022. In addition to national trends, the analysis also focuses on the regional NUTS2 level. In European terms, Hungary is characterised by a medium tourism performance, but tourism is still the dominant industry at the level of the national economy in terms of its contribution to GDP. The research highlights regional differences in socio-economic indicators and their correlation with economic determination and tourism performance. Indeed, the over-domination of Budapest can be identified in most socio-economic indicators. The consequence of the capital’s ’hydrocephalus’ is that Hungary’s peripheral regions have developed serious economic challenges. Reducing regional disparities in these areas is key to promoting economic catching-up and avoiding social tensions, in particular depopulation. The indicators presented in the study show a significant decline in the years after 2008 and in 2020-21 compared to previous years. This is attributable to the global economic crisis and the coronavirus pandemic, which have had a significant impact on the overall economic and tourism performance of our country.